An Overview of Spiritual Needs on Patient’s Anxiety Levels Diagnosed with COVID-19 in Hospital - Sevtri Ledyana Haloho; Ernawati Siagian (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2021)
Background: Spiritual needs have a relationship with the level of anxiety related to a person's body and soul to improve coping in dealing with difficult situations. Objectives: The purpose of this study is to describe variable attributes, spiritual needs, and anxiety levels in patients diagnosed with COVID-19. Methods: The research method is correlational descriptive using a purposive sampling technique, with a total of 155 respondents. The Spiritual Needs Questionnaire was used to measure spiritual needs and the Depression Anxiety Stress Scale was used to measure anxiety levels. Results: The research method is correlational descriptive using a purposive sampling technique, with a total of 155 respondents. The Spiritual Needs Questionnaire was used to measure spiritual needs and the Depression Anxiety Stress Scale was used to measure anxiety levels. Conclusion:Spiritual support as a means of coping and managing anxiety is needed to strengthen patients and families in overcoming their illness during the COVID-19 pandemic